Healthcare access and adverse family impact among U.S. children ages 0-5 years by prematurity status - Olivia J. Lindly; Morgan K. Crossman; Amy M. Shui; Dennis Z. Kuo; Kristen M. Earl; Amber R. Kleven; James M. Perrin; Karen A. Kuhlthau (BMC, 2020)
Abstract Background Many children and their families are affected by premature birth. Yet, little is known about their healthcare access and adverse family impact during early childhood. This study aimed to (1) examine differences in healthcare access and adverse family impact among young children by prematurity status and (2) determine associations of healthcare access with adverse family impact among young children born prematurely. Methods This was a secondary analysis of cross-sectional 2016 and 2017 National Survey of Children's Health data. The sample included 19,482 U.S. children ages 0-5 years including 242 very low birthweight (VLBW) and 2205 low birthweight and/or preterm (LBW/PTB) children. Prematurity status was defined by VLBW (i.e., < 1500 g at birth) and LBW/PTB (i.e., 1500-2499 g at birth and/or born at < 37 weeks with or without LBW). Healthcare access measures were adequate health insurance, access to medical home, and developmental screening receipt. Adverse family impact measures were ≥ $1000 in annual out-of-pocket medical costs, having a parent cut-back or stop work, parental aggravation, maternal health not excellent, and paternal health not excellent. The relative risk of each healthcare access and adverse family impact measure was computed by prematurity status. Propensity weighted models were fit to estimate the average treatment effect of each healthcare access measure on each adverse family impact measure among children born prematurely (i.e., VLBW or LBW/PTB). Results Bivariate analysis results showed that VLBW and/or LBW/PTB children generally fared worse than other children in terms of medical home, having a parent cut-back or stop working, parental aggravation, and paternal health. Multivariable analysis results only showed, however, that VLBW children had a significantly higher risk than other children of having a parent cut-back or stop work. Adequate health insurance and medical home were each associated with reduced adjusted relative risk of ≥$1000 in annual out-of-pocket costs, having a parent cut-back or stop work, and parental aggravation among children born prematurely. Conclusions This study's findings demonstrate better healthcare access is associated with reduced adverse family impact among U.S. children ages 0-5 years born prematurely. Population health initiatives should target children born prematurely and their families.